2017
DOI: 10.1111/tra.12529
|View full text |Cite
|
Sign up to set email alerts
|

CDK5‐dependent activation of dynein in the axon initial segment regulates polarized cargo transport in neurons

Abstract: The unique polarization of neurons depends on selective sorting of axonal and somatodendritic cargos to their correct compartments. Axodendritic sorting and filtering occurs within the axon initial segment (AIS). However, the underlying molecular mechanisms responsible for this filter are not well understood. Here, we show that local activation of the neuronal-specific kinase CDK5 is required to maintain AIS integrity, as depletion or inhibition of CDK5 induces disordered microtubule polarity and loss of AIS c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
39
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 74 publications
3
39
0
Order By: Relevance
“…Consistent with previous studies (7779), we have demonstrated that CCT acted on CDK5 to modulate retrograde axonal transport. It is possible that CDK5 signals through a mechanism involving dynein regulators Ndel1/Lis1 to stimulate retrograde axonal transport (77).…”
Section: Discussionsupporting
confidence: 93%
“…Consistent with previous studies (7779), we have demonstrated that CCT acted on CDK5 to modulate retrograde axonal transport. It is possible that CDK5 signals through a mechanism involving dynein regulators Ndel1/Lis1 to stimulate retrograde axonal transport (77).…”
Section: Discussionsupporting
confidence: 93%
“…In the proximal axon of fly sensory neurons, Golgi outposts co-localize with the dynein co-factor NudE, which likely functions with dynein to localize outposts to dendrites (Arthur et al, 2015;Lin et al, 2015;Ye et al, 2007;Zheng et al, 2008). The mammalian NudE ortholog Ndel1 is proposed to "catch" dendritic cargos and prime them for dynein-mediated transport into dendrites (Klinman et al, 2017;Kuijpers et al, 2016). We found that simultaneously decreasing dynein activity and kinesin-1 autoinhibition resulted in ectopic axonal Golgi outposts.…”
Section: Discussionmentioning
confidence: 83%
“…The loss of dynein activity alters both Golgi outpost localization and axonal microtubule polarity (Arthur et al, 2015;del Castillo et al, 2015;Klinman et al, 2017;Rao et al, 2017;Zheng et al, 2008). We first asked whether the misoriented microtubules in dynein loss-of-function neurons depend on the ectopic Golgi outposts.…”
Section: Loss Of Gm130 Significantly Reduces Misoriented Microtubulesmentioning
confidence: 99%